Investing in European Public Goods While Maintaining Fiscal Discipline at Home - Age Bakker; Roel Beetsma; Marco Buti (Intereconomics, 2024)
Putting the high public debt ratios on a downward path after the surge during the pandemic and allocating sufficient resources to deliver on the green and digital transition will be among the priorities confronting the EU institutions emerging from the June 2024 European elections. After a long and painful debate, EU institutions have agreed upon a new fiscal rulebook that aims to incentivise the reallocation of national public spending to the green and digital transition. However, the additional public investment is unlikely to suffice to comply with the goals of net zero that the EU has set for itself. In particular, investments of a transnational nature will remain undersupplied. This article proposes setting up a successor to NextGenerationEU - a new EU fund until 2030 for financing European public goods (EPGs) to address the double transition. Access to the facility would be conditional on adherence to the EU fiscal rules. By tying up the implementation of the new fiscal framework, the debate on the future of NextGenerationEU and the next multiannual EU budget post-2027, the credibility and internal consistency of these various instruments will be greatly enhanced.
Keywords: E22; E6; 330; Public goods; Budget consolidation; EU countries; Öffentliche Güter; Haushaltskonsolidierung; EU-Staaten